AKTIF DAN KREATIF DALAM PEMAMFAATAN GADGET SEBAGAI SARANA PEMASARAN DI DUNIA VIRTUAL - Methanti, Ayu (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
This research was conducted because in this modern and sophisticated era with various facilities it can increase student interest in entrepreneurship on social media. Motivating students to maximize the use of gadget technology even though it has limitations. It is expected that students can act more actively and creatively in solving problems due to inadequate facilities and infrastructure. In order to be able to compete in the midst of competitors even though the device used is only a smartphone.